(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Tidal stream energy is fast becoming a viable utility scale energy source for the UK and other resource rich countries. In the pluralistic tidal energy industry it is important that valid comparisons can be made between tidal energy converters on key metrics like power performance. The energetic and turbulent flow features conducive to a real tidal stream site pose challenges to the characterisation of incident inflow velocities when assessing the performance of an electricity-producing tidal energy converter. This study uses data from three concurrent Acoustic Doppler Current Profilers (ADCPs) placed upstream, and across the span, of a transverse axis crossflow tidal turbine to determine the effect of span-wise ADCP location on inflow velocity measurement. The 5 m span by 1.8 m diameter transverse axis crossflow turbine was deployed at the Queen’s Marine Laboratory (QML) tidal test site in the Strangford Narrows, UK, in Autumn 2024 for a 22-day test campaign experiencing peak flow speeds of up to 2 m/s. An assessment of the applicability of standards in the measurement of incident flow to a transverse axis crossflow turbine is presented. This study shows that span-wise inflow variation across the turbine swept area can be at magnitudes relevant to the power performance assessment criteria. This study adds to the evidence base indicating that turbines with large or non-circular swept areas face difficulties in the standardisation of incident flow measurement, issues not captured by the incumbent standards. Demonstrating the effect of ADCP location on inflow measurement of a transverse axis crossflow turbine enables informed sensor deployment for developers looking to appropriately characterise turbine performance.